THE CORINI ACTIVE FAULT IN SOUTHWESTERN VIOTIA REGION, CENTRAL GREECE: SEGMENTATION, STRESS ANALYSIS AND EXTENSIONAL STRAIN PATTERNS - Ganas, A.; Spina, V.; Alexandropoulou, N.; Oikonomou, A.; Drakatos, G. (Bulletin of the Geological Society of Greece, 2007)
The Corini normal fault is an active structure of Quaternary age in Southwestern Viotia. This is a region of low finite strain, located between the Quaternary rifts of the Gulf of Corinth and the Gulf of Evia. The fault is segmented into several segments with an average strike of N58°E and dip direction to the SE. The architecture of the fault zone is characterized by a 15 cm thick gouge rock, observed along the fault plane on the footwall side. At several localities along strike we observed a well-defined basal strip of un-eroded fault plane that represents the width (uplift) of the last co-seismic slip. The width of the strip ranges 20-30 cm. Slip inversion data show a mean orientation ofsigmaS (leastprincipal stress) as Ν328Έ which implies similar kinematics with the active faults of the south coast of the Gulf of Corinth.